Insect ecology - Price, Peter W. (New York : Wiley, 1997)
Insect Ecology is the world's foremost reference to the never-ending and crucial interactions of the richest taxon of organisms on this earth, with perhaps some 8 million extant species. Now in its Third Edition and twentieth year of publication, Insect Ecology has endured as an unparalleled classic.
Taking the reader from an explanation of the science to its significance as a discipline, Insect Ecology is a meticulous, systematic examination of the underlying dynamics of plant-insect interactions, predation, parasites and hosts, and mutualistic relationships, including pollination ecology, that are central to understanding the insects' role in nature.
Viewing the largely invisible drama of natural protagonists and antagonists, hidden in the lush foliage of a tropical rain forest or temperate woody vegetation, Peter Price details the unique traits, behaviors, and functions of insects, while placing them in the broader contexts of their places in food webs, ecosystem function, population dynamics, and community interactions.
Pt. IV. Communities and Distributions. Ch. 20. The Niche Concept and Division of Resources. Ch. 21. Intraspecific and Interspecific Competition. Ch. 22. Community Development, Structure, and Organization. Ch. 23. Diversity and Stability. Ch. 24. Paleoecology, Biogeography, and Biodiversity.
Includes bibliographical references and index.
Keywords: Insects -- Ecology